Kontribusi Dispora Bintan Dalam Pengembangan Kapasitas SDM Generasi Muda Melalui Ekosistem Kewirausahaan: Developing The HR Capacity - Wahyu Hidayat. R; Mirza Ayunda Pratiwi; Arjuni Rahazumardi; Rosevel Rompis; Jaya Samudra (Jurnal Archipelago, 2024)
This study examines the role of the younger generation in economic development through entrepreneurship in Bintan. The main issue is the low interest among youth in entrepreneurship, despite the existence of entrepreneurship training programs. The research aims to evaluate the contribution of the Bintan Youth and Sports Department (Dispora) in enhancing human resource capacity through the entrepreneurial ecosystem. A gap analysis shows an increase in the number of young entrepreneurs, but this number is still small compared to the total youth population. The novelty of this research lies in the specific analysis of Dispora Bintan's contribution, which has not been extensively studied. This program also plays a role in achieving regional development goals, particularly in improving the quality of competitive youth. The research uses a qualitative approach with a case study method. Data were collected through interviews and secondary data analysis to gain an in-depth understanding of the impact of the entrepreneurship program. The results indicate that Dispora Bintan's entrepreneurship training program has successfully increased the number of young entrepreneurs. However, the main challenge remains in broadening youth interest in entrepreneurship. Continuous evaluation and collaboration with local business actors are necessary to strengthen the entrepreneurial ecosystem in Bintan.